1988
DOI: 10.1254/jjp.48.157
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR Studies of Calmodulin: The Modifying Effect of W-7 (N-(6-Aminohexyl)-5-Chloro-1-Naphthalenesulfonamide) on the Calcium-Induced Conformational Changes of Calmodulin

Abstract: Abstract-The effect of W-7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(10 reference statements)
2
2
0
Order By: Relevance
“…The methionine methyl peaks are labelled by Arabic numerals. These numbers cor respond to those in our previous reports(12,15). Me t+: various divalent cations.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The methionine methyl peaks are labelled by Arabic numerals. These numbers cor respond to those in our previous reports(12,15). Me t+: various divalent cations.…”
supporting
confidence: 92%
“…It was thought, therefore, that an interface for the binding of calmodulin to the regulatory sites on target enzymes exists in the vicinity of the high-field corresponding residues and that they play an important role in many intracel lular calcium-dependent functions. The loca tions of the interface on calmodulin for target enzymes has been suggested in our other serial report (15). It shows that they exist in the hydrophobic amino acid residues of Cat+ binding sites II, III and IV (numbered from N-terminus).…”
Section: Discussionmentioning
confidence: 58%
“…The inhibitory propensities of W 7 also suggest that those residues on CaM with which it interacts are also important in regulating its binding to target enzymes. This study confirms previous observations of the similarity of the effects of Ca2+ and Cd2+ on CaM (8)(9)(10), and of the effects of W-7 on the Cat+-saturated protein (22,23). In addition, we have shown that W-7 affects Cd2+-saturated CaM in a very similar fashion by a detailed comparison of the changes which it induces in the spectrum of each metal-bound form of the protein.…”
Section: Discussionsupporting
confidence: 90%
“…(15). Previous studies (22,23) by 1H-NMR of W-7 binding to Ca2+-bound CaM suggest that W-7 interacts with hydrophobic amino acid residues in the vicinity of the cal cium-binding sites of domains II, III and IV and influences those. The effects exerted by W-7 appear similar to those of trifluoperazine (a CaM antagonist with other pharmacologi cal properties), D600 (a calcium channel blocker and CaM antagonist) and oxmetidine (a histamine H2 antagonist), whence it may be inferred that they bind to similar regions of the protein.…”
Section: Discussionmentioning
confidence: 93%